Aplicação de dados Lidar na caracterização geomorfológica de cavernas na porção sul da bacia de Irecê-BA - Moura, Pedro Edson Face (2022)
The present work, structured in three parts, has as its main objective to analyze three caves, namely Ioiô, Diva de Maura and Paixão, from the perspective of geomorphological phenomena, subsidized by data extracted from of point clouds, in order to establish a classification for the types of ornamentation present in the cave, taking into account structural control factors, associated with morphometric data and their variations through the geometry of the ceilings and the response of the speleothems in the formation of this cave. ornamentation. In part I, a bibliographic review of the concepts and definitions that encompass the systemic perspective of karst is carried out. Part II discusses Lidar data and its application in cave geomorphology, demonstrating the use of morphometric indices in the automatic extraction of cave features. In the third part of this work, the classification of cave ornamentation is suggested and applied, based on the morphology of the speleothem groups, on the place where they develop and on the predominant development process. The data obtained from this research allowed to show the different applicability obtained through the processing and manipulation of the point clouds obtained, either by Lidar or by Photogrammetry. These results point to new perspectives for the analysis of the internal features of the cave, which can be expanded beyond the ceiling ornamentation, encouraging discussions about these environments.